2003
DOI: 10.1590/s1413-81232003000200007
|View full text |Cite
|
Sign up to set email alerts
|

Atenção Básica e Programa de Saúde da Família (PSF): novos rumos para a política de saúde e seu financiamento?

Abstract: Este artigo examina a estratégia adotada pelos gestores federal e estadual do SUS, que prioriza a destinação dos recursos financeiros ao nível de Atenção Básica e ao Programa de Saúde da Família (PSF). Destaca-se a expansão dos recursos federais aos municípios, em forma de incentivos, destinados especialmente à Atenção Básica e ao PSF. O artigo salienta, também, a alocação de recursos dos estados a esse nível de atenção de saúde e a esse programa, identificando, particularmente, as formas de incentivos dos gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
28

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 1 publication
0
9
0
28
Order By: Relevance
“…This has occurred under circumstances of instability and uncertainty regarding public funding not being remedied 10,11 . Increased participation of states and municipalities in financing the Unified Health System through binding of minimum fundraising resources of each federative entity on Public Health Actions and Services (ASPS) has become one of the main alternatives to solve, or even remedy, underfunding 12 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This has occurred under circumstances of instability and uncertainty regarding public funding not being remedied 10,11 . Increased participation of states and municipalities in financing the Unified Health System through binding of minimum fundraising resources of each federative entity on Public Health Actions and Services (ASPS) has become one of the main alternatives to solve, or even remedy, underfunding 12 .…”
mentioning
confidence: 99%
“…This assertion needs to consider the specificities of subnational units. Studies have shown variations between municipalities regarding budget allocation in the health sector, especially given the socioeconomic diversity and the different liability profiles assumed by them regarding service provision, producing inequalities between them 9,11,12 . Data from municipalities of Mato Grosso indicate that the general budget composition of municipalities varies widely according to their size, especially with regard to revenues generated from their own taxation and Union transfers 17 .…”
mentioning
confidence: 99%
“…Descritores Descritores Descritores Descritores Descritores: Atención prenatal; Salud de la Mujer; Servicio de salud. (2) . Esses dados expressam a melhoria da oferta de serviços prestada pelo PSF, o que colaborou diretamente no aumento da utilização destes serviços pela população, e conseqüentemente uma melhor cobertura na assistência pré-natal.…”
unclassified
“…Além de terem a oportunidade de vivenciar a realidade da Atenção Básica na prática, eles refletem sua definição teórica, que se resume num conjunto de ações que dão consistência prática ao conceito de vigilância em saúde, indicatório que articula conhecimentos e técnicas oriundos do planejamento, redefinindo as práticas em saúde, articulando as bases de promoção, proteção e assistência, a fim de garantir a integralidade do cuidado. 15 A atenção e a proteção básica representam um campo de intersecção entre o SUS e o SUAS, onde ambos espaços convergem para o mesmo objetivo: a promoção da saúde e o restabelecimento de vínculos afetivos e sociais. São fortalecidas ações que apoiem a autonomia dos indivíduos, da família e da comunidade, considerando a atuação comum dos dois sistemas sobre os determinantes sociais e de saúde em um mesmo território.…”
Section: A Disciplina Saúde Da Comunidadeunclassified